Modified Chip-Evacuation Force Modeling and Chip-Clogging Prediction in Drilling of Cortical Bone - Airong Zhang; Song Zhang; Cuirong Bian; Hui Kong (IEEE Access, 2019)
Chip clogging is one of the fundamental issues faced by the dentists during the drilling of cortical bone. The chip clogging can lead to significant increase in temperature, thrust force and torque, and can even cause the drill bit to break. In this study, a modified chip-evacuation model to estimate the thrust force was developed for drilling of the cortical bone. First, the modified chip-evacuation force model with two parameters was developed based on the flute geometry. A set of drilling tests was conducted to calibrate the model parameters. Secondly, the parameter models were established as functions of spindle speed and feed, and the coefficients were then determined through nonlinear-regression analysis. The importance of cutting parameters on the model parameters was investigated via analysis of variance. Thirdly, the validity of the force model was analyzed by experimental results. Subsequently, based on the gradient of the chip-evacuation force, the chip-clogging prediction was conducted, and the prediction accuracy was assessed by the validation tests. Finally, the effect of cutting condition on the chip clogging was explored. The modified chip-evacuation force model proved to be an effective tool for predicting the thrust force, and the chip clogging could be estimated accurately with a relative error less than 10%. The spindle speed and the feed both had significant effects on the chip-evacuation force and chip clogging. The modified model could provide a better approach to finding how a pecking cycle can be implemented, and then, it can assist surgeons in selecting cutting conditions.